Advances in Intelligent Control and Engineering Applications - Eloy Irigoyen; Javier Sanchis; Pedro Cabrera (Applied Sciences)
Intelligent control is a discipline that is progressively maturing and has a real and significant transfer in a multitude of industrial applications and other engineering sectors today [...]